Review on Chinese agricultural science and technology research from a low-carbon economy perspective: hotspots, evolution, and frontiers - Jin, Weibo; Wu, Shiping; Zhang, Yi; Zhou, Gang; Xu, Lijie; Xu, Yao (Frontiers in Environmental Science, 2023)
Against the background of global climate change, agricultural science and technology play a vital role in achieving a low-carbon economy and sustainable development. Based on the research data of agricultural science and technology in Web of Science and China National Knowledge Infrastructure, adopting the bibliometric method, a knowledge graph was drawn using CiteSpace software; this paper analyzes the hotspot distribution, structural relationship and evolution process context while also comparing the difference between China and abroad from 1998 to 2023. The results indicate that existing research is mainly distributed in the following core modules, namely, agricultural science and technology, industrialization, modern agriculture, low-carbon agriculture, etc. The evolution of the research context features three stages: the traditional agricultural, current agricultural, and high-quality agricultural stages respectively. Research in China and abroad demonstrates both overlaps and differences in terms of knowledge structure, and such differences are related mainly to the concept of low-carbon agriculture, a variety of research perspectives, and the agricultural science and technology system. To expand the knowledge structure, deepening the research on, respectively, the evaluation and measurement of agrarian carbon footprint, micro-production entities, and strengthening international agricultural science and technology cooperation are innovative directions for future studies. This article systematically reviews agricultural scientific research from the perspective of a low-carbon economy, providing a reference point for the green and low-carbon transformation of agriculture in every country.